PENGEMBANGAN MEDIA FLIP CHART TERHADAP KETERAMPILAN MEMBACA INTENSIF SISWA KELAS III SEKOLAH DASAR - Sagnes Achriyati; Rina Yuliana; Lukman Nulhakim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses how to develop a Flip Chart as a means of motivation to enhance vocabulary in intensive reading class activities for third-grade elementary school students, to determine the feasibility of the developed Flip Chart, and to determine students’ responses to Flip Chart. The research was conducted at SD Negeri Secang by involving 30 third-grade students with 10 people in detail in a limited trial. The type of research refers to as the Borg and Gall model, which was modified by Sugiyono. This model consisted of six stages, problem analysis, data collection, product design,design validation, design revision, and product trials. The instruments used were media validation questionnaire used by the lecturer and a student questionnaire sheet. Based on the data analysis, it could be summarized that the quality of the developed Flip Chart as media was categorized in the very feasible category with a percentage of 85% based on the two media experts, the very feasible category with a percentage of 81.5% from two linguists, and 90.5% obtained from two material experts. Students’ responses to Flip Chart as media in the trial with 10 respondents were 84% in the very good category.